Dominant Factors Affecting Employment Opportunities in Indonesia - Muhammad Nur Afiat; Ahmad Ahmad; Muhamad Armawaddin (Jurnal Ekonomi dan Studi Pembangunan, 2024)
The Classical and Keynesian debate over the equilibrium of the open economy continues today. This research uses Keynes's theory of income and Cobb-Douglas's theory of production. The purpose of this study is to examine and analyze the partial effect of consumption expenditure, government expenditure, investment, and net exports on employment opportunities in Indonesia. In particular, this study knows the dominant factors that affect employment opportunities in Indonesia. The data type uses panel data from 33 provinces and the period 2010-2022. Data analysis using panel data regression and selection variables and stepwise least square forward.The results found that the best panel data regression estimation model is the "Fixed Effect Model (FEM)". The results of the influence test found that consumption expenditure, government spending, investment, and net exports were significant to employment opportunities. Only the variable direction of influence of government spending is negative. Of the four predictor variables, the consumption expenditure variable is the most dominant in influencing employment opportunities in provinces in Indonesia in 2010-2022.